Contributions of CH4-amine interactions by primary, secondary, and tertiary amines on CO2/CH4 separation efficiency - Wadi, Basil; Li, Chenhao; Manovic, Vasilije; Moghadam, Peyman; Nabavi, Seyed Ali (Elsevier, 2023)
In designing amine-incorporated adsorbents for CO2/CH4 separation, it is essential to understand the individual effects amine moieties have on the separation of CO2/CH4 mixtures. In this work, primary, secondary, and tertiary amines are moderately grafted on SBA-15 to examine factors affecting adsorption of CO2 and CH4. Materials were characterised by thermogravimetric and elemental analysis, and their performance was measured by volumetric and gravimetric gas adsorption. An amine density of 1.6–1.7 mmol/g in secondary and tertiary amines showed an equivalent CH4 uptake of <0.04 mmol/g at 25 °C, while primary amines adsorbed 0.05 mmol/g, indicating stronger interaction forces with CH4. In terms of selectivity, primary and secondary amines grafted at 1.3–1.4 mmol/g had similar values, unaffected by amine type. Adsorption results cross analysed with DFT simulations indicate similar binding energies for CH4 by both amine moieties, concluding the facilitated access of gas molecules to primary amine moieties is the primary factor dictating degree of adsorption. At an amine density of ∼ 1.7 mmol/g for both primary and secondary amines, an increase in temperature from 25 to 40 °C at a CO2 partial pressure of 40 kPa showed a decrease in CO2/CH4 selectivity of only primary amines. Secondary amines are thus more selective amine moieties at these conditions. Furthermore, in isothermal adsorption–desorption conditions, moderately grafted secondary amines have an equal working capacity to primary amines. Both these qualities support secondary amines at moderate densities as candidates for adsorbent development in CO2/CH4 separations.
Keywords: CH4 separation; Amine grafting; Primary amine; Secondary amine; Tertiary amine; Adsorption